LOVE EXPRESSIONS FOUND IN TWILIGHT NOVEL BY STEPHENIE MEYER: A PRAGMATICS ANALYSIS - HAPSARI , MILLA WIDYA (2011)
This study deals with: (1) the type of sentence for love expressions in Twilight novel and (2) the function of love expressions in Twilight novel . The type of this research is descriptive qualitative research, by which the object is love expressions Twilight novel by Stephenie Meyer. In order to collect the data, the writer must, firstreading the novel. Second, finding the words or sentences of Love Expressions.Third, underlying the words or sentences of Love Expressions.Fourth collecting the words or sentences that related with the speech act of Love Expressions. And the last giving codes the data. The results of the study shows that, (1) there are three types of sentence for love expressions, they are declarative sentence (as long as you want me, "he assured me) interrogative sentence (do you swear you won't leave me? "I whispered), and imperative sentence (don't worry about me, "I urged). (2) there are six functions of love expressions, namely showing affection (I love you, "I whispered), showing care (take care, "Billy warned me), showing engagement (I'll be there, "I promised) showing persuasion (don't worry about me, "I urged ), showing eagerness (you really should stay away from me, "he warned ), and showing praise (that's really nice, Dad "I really appreciate it).